Analisis Terhadap Tugas dan Fungsi Jaksa Sebagai Pengacara Negara dalam Perkara Perdata - Bambang Hartono (KEADILAN PROGRESIF, 2012)
In running duty, function and authority of Public attorney pursuant to particular full power to conduct action and legal aid in and also extrajudical deputize importance of civil of state, governmental and society. Referring to this matter problems of this writing  is Attorney function and duty as Public Prosecutions in civil dispute This research use method approach of empiric and normatif, source of data of sekunder Data collecting primary data and bibliography study and field study and analysis qualitative. Result of research indicate that Attorney function and duty as Public Prosecutions in civil dispute for example as straightening of law, giving legal aid, giving consideration of law, giving service of law, and conduct action other law.